Estrategias para el desarrollo de la creatividad de los niños y niñas de quinto grado de educación básica, en la unidad educativa Lauro Damerval Ayora n°2 de la cuidad de Loja período lectivo 2013 - 2014 - Rojas Betancourt, Yomaira Lisbeth (2016)
The investigation takes as an intention to analyze of what way the model of managing professional performance optimizes the educational management for results, of the School of Baccalaureate Rafael Rodríguez Palacios, of the parish Malacatos, Canton and Province of Loja. Academic period 2014-2015. Trying to obtain excellent information that he contributes to the problems solution in this educational community. The used methodology was the descriptive one managing to detail the current situation of the problem; bibliographical allowing to find information specific and determined; analytical – synthetic where there was done a critical study of the obtained information, allowing to organize appropriately the information, establish conclusions and alternative lineaments; the statistics, facilitated the representation on a graph of the information, and the arithmetical average for the ratification of the results. The population shaped by a manager, fourteen teachers, 280 students and fifty family parents. The used skills the guide of interview and the survey. The instrument a questionnaire with a scale structured with 10 items. As main result obtained that 86 % of the polled population demonstrates that the manager does not demonstrate in its management a solid professional training. One concluded that it does not frame its managing management in the standards of managing professional performance proposed by the Department of Education. Therefore, one recommends that to be faced the organization by intentions, common values, goals and clearly established and shared targets, planned, systematical and deliberate actions, for it a favorable labor climate must exist exercising a good leadership in procure of a managing advanced post management.